Quality Function Deployment, Value Engineering and Target Costing, an Integrated Framework in Design Cost Management: A Mathematical Programming Approach - Jariri, F; Zegordi, S H (Scientia Iranica, 2008)
In this paper, the need to incorporate three famous design cost management methods, called: Quality Function Deployment (QFD), Value Engineering (VE) and Target Costing (TC) into a single model has been addressed. Each method performs very well in cost management procedures as design activities. These methods have been incorporated into a mathematical programming model, in order to achieve the maximum benefit of each method. The model, essentially, optimizes customer satisfaction subject to target cost. The tool is a mixed integer zero-one nonlinear programming. The unified model has been proposed to prevent a non-optimal solution when methods interact with each other. The practitioner should be confident that the quality solution would be achieved in contrast to when the methods are applied sequentially. A simple automobile design example was formulated and solved to show the performance of the model.